The Impact of Specific Language Impairment (SLI) in 6-Year-Old Children - Sholihatul Hamidah Daulay; Khairun Niswa; Tara Pratiwi; Khairunnisa (Universitas Nahdlatul Ulama Surabaya, 2022)
This study focuses on the discipline of psycholinguistics regarding language disorders in children, to be precise of Specific Language Impairment (SLI). This article analyzes two 6-year-old children who show the characteristics of having SLI in language disorders during the COVID-19 pandemic. In order to carry out this study, the researcher used a qualitative descriptive research method. The method aims to describe in a systematic, actual, and accurate way. This research is an analytical study of official documents such as books, articles, journals, and the internet. The accuracy of the data is obtained from the observations of the researcher herself. This study reports that children with SLI often stay until school age and can lead to a lack of academic ability and cause various psychosocial problems. Some of the causes of SLI in children include genetic, environmental, and social factors, pre and perinatal, gender, prematurity, weight, socio- economic status, maternal mental status, mother's education, and vocabulary, and  history of speech-language difficulties.